Evolution of the banana genome (Musa acuminata) is impacted by large chromosomal translocations - Martin, G.; Carreel, F.; Coriton, O.; Hervouet, C.; Cardi, C.; Derouault, P.; Roques, D.; Salmon, F.; Rouard, M.; Sardos, J.; Labadie, Karine; Baurens, F.C.; et al. (Oxford University Press, 2017)
Most banana cultivars are triploid seedless parthenocarpic clones derived from hybridization between Musa acuminata subspecies and sometimes M. balbisiana. M. acuminata subspecies were suggested to differ by a few large chromosomal rearrangements based on chromosome pairing configurations in inter-subspecies hybrids. We searched for large chromosomal rearrangements in a seedy M. acuminata ssp. malaccensis banana accession through mate-pair sequencing, BAC-FISH, targeted PCR and marker (DArTseq) segregation in its progeny. We identified a heterozygous reciprocal translocation involving two distal 3 Mb and 10 Mb segments from chromosomes 01 and 04, respectively, and showed that it generated high segregation distortion, reduced recombination and linkage between chromosomes 01 and 04 in its progeny. The two chromosome structures were found to be mutually exclusive in gametes and the rearranged structure was preferentially transmitted to the progeny. The rearranged chromosome structure was frequently found in triploid cultivars but present only in wild malaccensis ssp. accessions, thus suggesting that this rearrangement occurred in M. acuminata ssp. malaccensis. We propose a mechanism for the spread of this rearrangement in Musa diversity and suggest that this rearrangement could have played a role in the emergence of triploid cultivars.